Digital Media And The Amplification Of Marginalised Voices In Select Communities In Akwa Ibom State - George Nathan Brown; Morah Doris Ngozi, PhD; Ifeanyi Martins Nwokeocha, PhD; Christian Ugochukwu EGEH; Promise Adaku Obi (International journal of technology and education research, 2025)
This study investigated the potential of using digital media to amplify marginalised voices in select communities in Akwa Ibom State, Nigeria. The objectives were to examine the extent to which digital media amplifies marginalised voices, identify the challenges faced by marginalised groups in utilising digital media, and explore strategies for enhancing the use of digital media to promote marginalised voices. The study was anchored on the Social Identity Theory and Technological Acceptance Model. The study adopted a survey research design, with a sample size of 399 respondents selected using Taro Yamane's formula. Data analysis revealed that 37% of respondents indicated that digital media